Isolation of the right subclavian artery in a patient with d-transposition of the great arteries - Alisa Arunamata; Stanton B Perry; Alaina K Kipps; Shreyas S Vasanawala; David M Axelrod (Wolters Kluwer Medknow Publications, 2015)
Isolation of the right subclavian artery (RSCA) is rare, and this finding in association with d-transposition of the great arteries (d-TGA) is extremely unusual. We present a case of an isolated RSCA in a newborn with d-TGA in whom the clinical presentation was diagnostic. We discuss the imaging modalities used to confirm the diagnosis, the embryological basis of the finding, and the surgical repair.